Exploring Teen Pregnancy as a Public Health Problem: A Critical Scoping Review of Public Health Research on Teen Pregnancy in Canada - Sherri Dutton; Mir Sanim Al Mamun; Colleen M. Davison (Societies)
Inequities related to teen pregnancy are a complex social and health problem across the globe. Evaluation of research assumptions can help to move research forward when considering complex public health issues. Drawing on previous critical reviews, this scoping review sought to map not just what teen pregnancy research is available, but how current public health research was orienting to teen pregnancy in Canada. This review included studies focused on general or intended teen pregnancy within a public health Canadian context. Both grey and peer-reviewed literature were searched, with only studies in English and French included. In total 32 studies were analyzed. Taking a multifaceted approach to assessing research orientation this scoping review applied an adapted health equity framework to consider alignment between awareness and action and utilized discourse analysis to explore constructions of pregnancy intention. Results showed although a portion of research fell within the acknowledge and illuminate categories, most of the research utilized public health language rooted in biomedical and individualistic discourses and focused on influencing individual action, rather than greater societal change. Adding to the growing body of teen pregnancy research in Canada, this scoping review revealed potential epistemological barriers related to limited research approaches, applied public health action, and engagement with topic overall, leading to a call for more diverse, critically reflective, and disruptive approaches to teen pregnancy research in Canada to address teen pregnancy-related inequities at the root.